NIPAH (NYPA FRUTICANS) UTILIZATION FOR BIO-ETHANOL AT DELTA MAHAKAM - Radita Arindya (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2017)
In the year 2007-2012, the Indonesian government target to replace 1.48 billion liters of gasoline with bio-ethanol. Currently a new bio-ethanol can be supplied as much as 137,000 liters per month (0.4%). Nipah (Nypa fruticans) is one of palm species that grows in the mangrove forest. Sugar from the sap of Nipah is high enough so that it is potential as a base for the production of bioethanol. Vegetable-based fuel or bio-ethanol can reduce environment pollution; due to its CO2 emissions are very low, making it more environmentally friendly. Bio-ethanol can be used as a substitute for fossil fuel. Bio-ethanol with levels of 95-99% can be used as material substitution for gasoline.